Analisis Kesesuaian Penggunaan Lahan dengan Rencana Pola Ruang di Kabupaten Ogan Ilir - Adianto, Muhammad Obby; Ar-Rouf, Ferdian Budi; Gustama, Muhammad Agni; Utami, Nyimas Ulfatry (Mataram University, 2026)
Abstract Ogan Ilir Regency is included in the development program as a buffer zone for Palembang City, which is part of the Sriwijaya Megaregion, due to its distance of approximately 35 km. Ogan Ilir Regency has established a Spatial Planning (RTRW) Plan for 2023–2024. This RTRW serves as the basis for policy direction and the development of urban areas. Therefore, research on spatial analysis is necessary to evaluate existing development. This study uses descriptive analysis with a spatial approach, namely a Geographic Information System (GIS). The software used is QGIS, which is open-source. The data sources include Sentinel satellite imagery and the Spatial Planning Map of Ogan Ilir Regency. The analysis applies supervised classification to identify existing land use. The results show that 11,461.4 hectares of land use are not in accordance with the Ogan Ilir RTRW. The largest area of inconsistency is found in North Indralaya District, which is planned as an urban area but is still predominantly used for oil palm agricultural land.